2019
DOI: 10.24106/kefdergi.3153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Conceptual Change Texts on Overcoming The Misconceptions in the Social Studies Courses

Abstract: Araştırmanın amacı, 7. sınıf öğrencilerinin "Türk Tarihinde Yolculuk" ünitesinde yer alan kavram yanılgıları üzerinde, kavramsal değişim metinlerinin etkisini incelemektir. Araştırmanın çalışma grubu, Kırşehir il merkezinde bulunan X ortaokulunda öğrenim gören 7/A ve 7/C sınıfı öğrencilerinden oluşturulmuştur. Bu sınıflardan 7/A deney (n:22), 7/C kontrol grubu (n:27) olarak belirlenmiştir. Araştırmada yöntem olarak, eşitlenmemiş kontrol gruplu desen kullanılmıştır. Kavramlar belirlenirken 7. sınıf sosyal bilgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
4
0
2
Order By: Relevance
“…This significant change was clearly presented in the concept definitions that the experimental group students made directly in their own writings. Similar results have been obtained in different studies in the literature conducted on conceptual change texts that contribute positively to the learning of the concepts in the field of active citizenship learning in the social studies course (Akbaş, 2008;Kılıçoğlu, 2011;Aladağ & Yılmaz, 2014;Yıldırım, 2016;Çelikkaya & Şarlayan, 2019;Kürümlüoğlu, 2019;Köroğlu, 2019;Sel & Sözer, 2019). There are important effects of conceptual change texts in the background of the conceptual change and development experienced by the students in the field of active citizenship learning in the social studies course.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 84%
See 2 more Smart Citations
“…This significant change was clearly presented in the concept definitions that the experimental group students made directly in their own writings. Similar results have been obtained in different studies in the literature conducted on conceptual change texts that contribute positively to the learning of the concepts in the field of active citizenship learning in the social studies course (Akbaş, 2008;Kılıçoğlu, 2011;Aladağ & Yılmaz, 2014;Yıldırım, 2016;Çelikkaya & Şarlayan, 2019;Kürümlüoğlu, 2019;Köroğlu, 2019;Sel & Sözer, 2019). There are important effects of conceptual change texts in the background of the conceptual change and development experienced by the students in the field of active citizenship learning in the social studies course.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 84%
“…As a result of that study, conceptual change texts proved very efficacious in increasing students' understanding of concepts and eliminating misconceptions. As another example, Yıldırım (2016) included conceptual change texts in the teaching process of five different concepts (e.g., management, public opinion, national sovereignty, national independence, democracy) in the social studies course to the fourth grade students, whereas Aladağ and Yılmaz (2014) included conceptual change texts to identify and eliminate existing misconceptions about concepts such as culture, national culture, and value contained in the fourth grade social studies curriculum. Both Yıldırım (2016) and Aladağ and Yılmaz (2014) reported that the process carried out through conceptual change texts enabled students to learn the concepts correctly.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed imbalance is thought to be caused by the inadequately organized learning environments and the insufficient concretization of concepts (Demirkaya & Karacan, 2016;. On the other hand, many studies on concept teaching in social studies (Akbaş & Toros, 2016;Akpınar, 2019;Akşit & Dinç, 2015;Akyol Gök, 2014;Çelikkaya & Şarlayan, 2019;Çolak, 2010;Demirci, 2019;Demirkaya & Karacan, 2016;Dere & Aktaşlı, 2019;Gültekin, 2016; demonstrated the effectiveness of graphic materials in concept teaching. Current studies recommend that social studies teachers should be given necessary in-service training in concept teaching (Akbaş, 2013;Akgün, 2014;Çelikkaya & Kürümlüoğlu, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…Bu nedenden dolayı, öğretim öncesinde, sırasında ve sonrasında öğrencilerin var olan kavramları ve düşünce türleri araştırılıp ortaya konmalıdır (Kabapınar, 2003). Son yıllarda öğrencilerin sahip oldukları kavram yanılgılarının giderilmesine yönelik çok fazla çalışma (Ayana, 2018;Boz, 2019;Kürümlüoğlu, 2019;Özdoğan, 2019;Şarlayan, 2017) yapılmakta ve farklı yöntemler kullanılmaktadır. Kavram yanılgısını giderme yöntemlerinden bir tanesi de She (2002She ( , 2004aShe ( , 2004b tarafından geliştirilmiş olan İkili Yerleşik Öğrenme Modelidir (İYÖM).…”
Section: Introductionunclassified